A simple risk‐based reimbursement system for kidney transplant. Issue 1 (24th September 2020) - Schwantes, Issac R.; Schnitzler, Mark A.; Lentine, Krista L.; Balakrishnan, Ramji; Reed, Alan I.; Axelrod, David A.
Abstract: Transplant centers were challenged by the Executive Order on Advancing Kidney health to increase access to kidney transplant (KTx) by accepting higher risk patients and organs. However, Medicare reimbursement for KTx does not include adjustment for major complicating comorbidities (MCCs) like other transplants. The prevalence of MCCs was assessed for KTx performed from 10/15 to 10/19 at a single academic center, using Medicare ICD10 MCC criteria exclusive of end‐stage kidney disease. KTx hospital resource utilization and estimated margin, assuming Medicare reimbursement, were determined for cases with and without MCC. Among 260 KTx recipients, 49 (19%) had an MCC. Patients with MCCs had longer wait times (1121 days vs 703 days, P  < .001); however, there were no differences in age, gender, race, or diagnosis. Donor characteristics associated with an MCC included greater cold ischemic time (1042 vs 670 minutes, P  < .001) and fewer living donor KTx (9% vs 32%, P  < .001). KTx cost, exclusive of organ acquisition, was 31% higher (MCC: $38 293 vs No MCC: $29 132) and estimated margin was markedly lower (‐$7750 vs ‐$1001, P  = .001). In conclusion, KTx with qualifying MCCs resulted in significant financial losses and modification of KTx payment methodology to align with other organ transplants is needed.